Urban land markets and land price changes a study in the Third World context - Kundu, Amitabh 1948- (Routledge, 2018)
First published in 1997, this study is one of the forerunners in the area of urban land market and land price studies on a Third World city, focusing on Lucknow City in Uttar Pradesh, India, and exploring house prices, economic changes and construction. Amitabh responds to the 2nd Habitat Conference of 1996, which realised that housing conditions for lower income group people in most Third World cities have not improved, especially with regards to tenure, affordability and overall housing quality
First published 1997 by Ashgate Publishing
Keywords: Land use, Urban / India / Lucknow; Real property / Prices / India / Lucknow; Housing / India / Lucknow; Land use, Urban / India; BUSINESS & ECONOMICS / Real Estate / General; BUSINESS & ECONOMICS / General; Housing; Land use, Urban; Real property / Prices; India; India / Lucknow